THE RELATIONSHIP BETWEEN KNOWLEDGE AND ATTITUDE TOWARD ANEMIA ON PREGNANCY IN LIMBOTO HEALTH CENTRE - Zuriati Muhamad (LPPM Universitas Muhammadiyah Gorontalo, 2019)
Anemia in pregnancy is a national problem because it reflects the value of the socioeconomic welfare of the community, and its influence is very large on the quality of human resources This research was conducted at Puskesmas Limboto. The purpose of this research is to findout the correlation of knowledge and attitude of Primigravida Pregnant Women with Anemia at Limboto Puskesmas Kabuapten Gorontalo. The type of this research is Descriptive Analytic with cross sectional approach with sample number 48 respondents. The sampling technique used is purposive sampling. From result of analysis of SPSS 16 statistical test of knowledge with anemia using Chi-square formula with significance level 0,05 obtained result 0.013 <0,05 which mean there is correlation of knowledge with anemia at Puskesmas Limboto Kabupaten Gorontalo. As well as attitudes with anemia obtained results 0.000 <0.05 which means there is a correlationbetween attitude with anemia in the Work Area Puskesmas Limboto, Gorontalo District.Anemia pada kehamilan merupakan masalah nasional karena mencerminkan nilai kesejahteraan sosial ekonomi masyarakat, dan pengaruhnya sangat besar terhadap kualitas sumber daya manusia. Penelitian ini dilakukan Puskesmas Limboto.Tujuan penelitian ini untuk mengetahui hubungan pengetahuan dan sikap ibu hamil primigravida dengan kejadian anemia di wilayah Puskesmas Limboto Kabupaten Gorontalo. Desain penelitian ini ini menggunakan kuantitatif dengan pendekatan cross sectional dengan jumlah sampel 48 responden.Teknik pengambilan sampel yang digunakan adalah purposive sampling. Hasil analisis uji statistik menunjukkan hubungan antara pengetahuan dengan kejadian anemia menggunakan rumus Chi- square dengan tingkat kemaknaan 0,05 diperoleh hasil 0.013 < 0,05 yang berarti ada hubungan antara pengetahuan dengan kejadian anemia di Wilayah Puskesmas Limboto Kabupaten Gorontalo. Serta ada hubungan antara sikap dengan kejadian anemia diperoleh hasil 0.000 < 0,05.